(untitled) (Journal of International Studies, 2020)
This paper presents current developments in Islamic banking and financial institutions in Malaysia. It begins by discussing the paradigm of Islamic banking and finance through the concept of Islam and economics, the emergence of Islamic financial institutions in Malaysia, the concept of AI-Bai’ Bithaman Ajil (BBA) and also the future direction of Islamic banking. The writer argues that Islamic banking is still within the framework of the conventional system except on the element of riba in its transaction. The growing number of products, systems, infrastructures and supporting institutions of Islamic banking in recent years may sustain the development of the Islamic banking industry. With the current issues in BBA, the industry needs to better understand the basic tools in Islamic banking and any weaknesses in today’s system should be rectified so as to help develop Islamic banks become truly innovative, competitive and integrated part of the contemporary global finance.